Design of a Printed Dipole Antenna Array for a Passive Radar System - Peter Knott (International Journal of Antennas and Propagation)
Passive radar (or Passive Coherent Localisation) is an advancing technology for covert operation. The signal transmitted from sources of opportunity such as radio or TV stations is used as illumination for a certain area of interest. Part of the transmitted signal is reflected by radar targets, for example, moving objects such as vehicles or aircraft. Typical radar parameters are derived from the comparison between the direct line-of-sight from the transmitter and the signal scattered from the target object. Such systems are an attractive addition to existing active radar stations because they have the potential to discover low-flying and low-observable targets and no active radar transmitter is required. Printed dipole antennas are very attractive antenna elements for such systems because of their easy fabrication, low-cost, polarisation purity, and low-profile properties. The present paper describes the design of an antenna array using printed dipole elements with flared arms for a passive radar system operating in the GSM900 frequency range. Isolated antenna elements and a small uniform linear antenna array were designed and optimised using computational electromagnetic methods. Several prototypes have been fabricated on conventional microwave PCB substrate material. Preliminary measurement results for antenna matching and far-field radiation patterns are shown.